Small molecule activation by multimetallic uranium complexes supported by siloxide ligands. Issue 87 (14th October 2019) - Barluzzi, Luciano; Falcone, Marta; Mazzanti, Marinella
Abstract : An overview of the small molecule activation chemistry of polynuclear complexes of uranium supported by the tert -butoxysiloxide ligand. Abstract : The synthesis and reactivity of uranium compounds supported by the tris- tert -butoxysiloxide ligand is surveyed. The multiple binding modes of the tert -butoxysiloxide ligand have proven very well suited to stabilize highly reactive homo- and heteropolymetallic complexes of uranium that have shown an unusual high reactivity towards small molecules such as CO2, CS2, chalcogens and azides. Moreover, these ligands have allowed the isolation of dinuclear nitride and oxide bridged complexes of uranium in various oxidation states. The ability of the tris- tert -butoxysiloxide ligands to trap alkali ions in these nitride or oxide complexes leads to unprecedented ligand based and metal based reduction and functionalization of N2, CO, CO2 and H2 .